(untitled) (Actualité en allergologie et en immunologie au Canada, 2024)
Atopic dermatitis (AD), also commonly referred to as atopic eczema, is the most common chronic inflammatory skin disease. Research over the past 30 years has revealed that it affects approximately 13% of children and 7% of adults worldwide. Among the growing number of treatment options for AD, the role of allergy to aeroallergens, such as house dust mite (HDM) pollens or animal dander, in driving this condition has remained uncertain for a long time. Consequently, so too has been the therapeutic role of allergen immunotherapy (AIT) for AD. The American Academy of Allergy, Asthma & Immunology (AAAAI)/American College of Allergy, Asthma and Immunology (ACAAI) Joint Task Force (JTF) on Practice Parameters recently updated their AD guidelines. This update included a systematic review of the effectiveness and safety of AIT, including subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT) versus no AIT for patients with AD. This article summarizes the systematic review findings, guideline update, and future directions.